Efektivitas Komunikasi dalam Penyuluhan Sistem Tanam Jajar Legowo pada GAPOKTAN Sumber Mulyo di Desa Kediren, Kecamatan Kalitengah, Kabupaten Lamongan, Jawa Timur - ACHMAD, VIVI ANITA; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2019)
Effectiveness of Communication in Counseling Jajar Legowo Planting System on GAPOKTAN Sumber Mulyo in the Village Kediren, Sub-district Kalitengah Lamongan Regency, East Java. Increased productivity of rice farming is needed in order of the community. The innovation of the Jajar Legowo planting system is expected to bring about an increase in the results of farming. One of the Gapoktan implementing Jajar Legowo planting system is GAPOKTAN Sumber Mulyo. Facts on the field show that rice yields using the Jajar Legowo planting system did not increase compared to using a tile system. This was allegedly due to communication carried out by extension agents to farmers. Farmers do not understand the explanation given by extension workers. Therefore, it is necessary to conduct research on communications conducted by extension agents.Communication can be effective if there is understanding, pleasure, attitude, good relationship, and action. The research location is located in Kediren Village, Kalitengah District, Lamongan Regency. The purpose of this study was to determine the effectiveness of communication in the extension of the Jajar Legowo planting system on GAPOKTAN Sumber Mulyo. The analytical method used is qualitative descriptive analysis.Based on the results of the study it can be concluded the extension of the Jajar Legowo planting system is effective. The effectiveness of the communication is shown by: (1) farmers understand the Jajar Legowo planting system; (2) farmers enjoy the Jajar Legowo planting system; (3) farmers sympathize with the Jajar Legowo planting system; (4) the relationship between farmers and extension workers is very good; and (5) the application of Jajar Legowo planting system in accordance with the recommendations of the instructor. Based on the results of the study, discussion, and conclusions, it can be suggested: (1) the need for counseling to members of GAPOKTAN Sumber Mulyo to use organic fertilizer in farming so that agricultural land remains fertile and can be used for mina rice; (2) farmers can revive a culture of mutual cooperation in planting so that it does not require large costs; (3) extension agents can conduct counseling using cyber extention methods is farmers can learn the material neeses through the internet.